COMBATTING CULTISM IN NIGERIA’S DIGITAL SOCIETY BY LEVERAGING YOUTHPRENUERSHIP FOR COMMUNITY DEVELOPMENT - CHIDI FRANKLIN UZOIGWE; OZINNA OKOYE (International Studies Journal)
It is obvious that literature abound on cultism, community development, youth and youthpreneurship but combating cultism in Nigeria’s digital society by leveraging youthpreneurship for community development is evidently not in existence, creating a gap which this paper seeks to fill by  exploring the multifaceted approach required to address cultism in Nigeria's digitalized society, highlighting the pivotal role of youth entrepreneurship in offering viable alternatives for positive youth engagement. It traces the historical roots of cultism and secret societies in Nigeria to the pre-colonial era, with particular focus on their emergence in university settings in 1952. The study aims to identify the underlying factors contributing to cultism and its detrimental impact on community development, advocating for the implementation of youthpreneurship initiatives as a solution. Employing a survey design, the research gathers quantitative data through questionnaires. Its findings indicate that cultism is deeply entrenched in Nigerian society, fueled by factors such as poverty, unemployment, and political instability. The paper recommends the effective implementation of youth development policies, including skills training, mentorship programs, and access to funding, to nurture entrepreneurial spirit among youth and foster innovation.